Sosialisasi Penggunaan Gadget melalui Media Pembelajaran dengan Metode Participatory Action Research - Suryopratomo, Anggit; Nisa, Dea; Saebah; M. Zaid (Ma'soem University, 2025)
Karyalaksana Village, Ibun District, Bandung Regency is one of the villages where most of the children already have gadgets, whether they are personal gadgets or those belonging to their parents. The rapid development of digital technology has made gadgets a part of modern life, including the lives of children. The problem that occurs in Karyalaksana Village is the lack of awareness that excessive use of electronic devices such as gadgets can have various negative impacts on health. This work program aims to educate children in Karyalasana Village about the negative impacts of excessive use of gadgets. The ac tivity method used PAR (Participacy Action Research) is through 3 stages Planning, Implementation, Result and Evaluation. The results of this service activity include participants being able to undrestand the impotance of limiting the use of gadgets in everyday life and introducing traditional games as a more useful alternative.